PRAKTIK MAGIS QS. ṬĀHĀ: 39 DENGAN BULU PERINDU: STUDI LIVING QUR’AN DI KABUPATEN KOLAKA - Nur Aeni Putri Gafar; Fatirawahidah; Akbar; Hasdin Has (EL-MAQRA', 2025)
This article examines the practice of implementing QS. Ṭāhā: 39 using bulu perindu as a medium of attraction in Kolaka Regency, Southeast Sulawesi, which aims to explore the form of practice, the process of transmission and transformation, and its impact on the function of the Qur'an as a guide (hudan). The method used by the author is a qualitative approach with the living Qur'an method, through observation and interviews. It was found that this practice varies, combining the reading of verses with the use of bulu perindu and water, and is influenced by religious stories. Knowledge is transmitted through families, religious teachers, and social media, while the transformation of this practice is seen in the focus of the verses and additional ritual media. The implications show the complex interaction between the sacred text and local culture sometimes showing quite obvious differences with the meaning of the verses specifically intended. The study recommends the formation of a study council so that the practice of the Qur'an remains in accordance with its function as a guide (hudan), but still respects local culture